Prevalence of anemia among female medical students and its correlation with menstrual abnormalities and nutritional habits - Kannan, Bhuvaneshwari; Ivan, Erli Amel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of iron deficiency anemia, which is the commonest cause for anemia, is 52% in Indian women aged 15 to 49 years, as per WHO statistics. Health consequences of anemia include reduced immunity, increased morbidity and impaired cognitive performance. Methods: The study participants were requested to fill in a pretested self-administered questionnaire. Under aseptic precaution 2 ml of venous blood sample was collected in EDTA vacuum tubes and tested for Hb%, PCV, RBC indices using automated analyzer - Pentra ES 60 and peripheral smear study was done by the pathologist. Results: Anemia was present in 43% of the study population with 37% having mild anemia. Hematocrit was less than normal in 36.2% of the study population with 32.2%showing hypochromia and 21.5% showing microcytosis, thus confirming iron deficiency status. Peripheral smear study revealed microcytic hypochromic blood picture in 26%, normocytic hypochromic in 38% and normocytic normochromic in 32% of the anemic subjects. Menorrhagia was present in 14% of the anemic students whereas 14.1% of the non-anemic subjects had oligomenorrhoea. Conclusions: Frequent screening of the students for the presence of anemia and regular health checkups is a must in all school and university students.